WTO Safeguards And Trade Liberalization : Lessons From The Argentine Footwear Case - Baracat, Elías (The World Bank, 2005)
The footwear case provides an example of the complexities of World Trade Organization (WTO) rules on the use of safeguards, and of the interaction of multilateral and regional processes of liberalization. As a result both of Argentina's unilateral liberalization and the removal of barriers within Mercosur, imports of footwear increased rapidly. As Mercosur provides no intra-regional safeguard mechanism, the government of Argentina responded by applying import relief and WTO safeguards against third countries. The WTO Dispute Settlement Body addressed these measures and as a consequence, Argentina dismantled most of them, leading to four main conclusions: The jurisprudence of the WTO's Appellate Body has created serious uncertainty as to when a country can use safeguards. This does not contribute to the political balance that has to be maintained when developing countries implement trade liberalization programs. In fact, it detracts from this crucial goal. It is an error to negotiate ambiguous multilateral agreements on the expectation that the WTO Dispute Settlement mechanism will clarify them. An overvalued currency heightened the industry's problems. In the case of footwear, the decline in imports following the recent devaluation was more important than that following the implementation of earlier relief measures. The political economy of liberalization also indicates the need for regional agreements to include adequate transition mechanisms that will facilitate adjustment to free trade and to maintain support for it